Efektivitas Media Pembelajaran Vistacreate dalam Meningkatkan Keterampilan Desain Grafis Murid Disabilitas Fisik - Muzakki Afif; Nurhastuti; Damri; Antoni Tsaputra (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Eighth-grade students with physical disabilities in SMPLB at SLBN Duri experience obstacles in digital graphic design skills, especially in the use of application features, visual element arrangement, and fine motor coordination when operating devices. This condition indicates the need for adaptive and easy-to-use learning media. This study aims to analyze the effectiveness of VistaCreate learning media in improving and maintaining the graphic design skills of students with physical disabilities. The study used a quantitative approach with the *Single Subject Research* (SSR) method and an A-B-A design which included the first baseline (A1), intervention (B), and second baseline (A2). The subject of the study was one student with physical disabilities. Data were collected through structured observations and performance tests using a 15-indicator instrument with a score rubric of 1–4, then analyzed visually within and between conditions. The results showed a trend towards an increase in phases A1, B, and A2, with a percentage range of 43%–48%, 56%–82%, and 82%–88%, respectively. Data from the intervention phase showed an 8% positive change in the learning level and 100% stability, while analysis between conditions showed a 34% positive change in the learning level and 0% overlap. These findings indicate that VistaCreate effectively improves and maintains the graphic design skills of students with physical disabilities.